Strategi Manajemen Keuangan Untuk Pelajar di Era Gen Z Bagi Siswa Smk Islam Darurrohman - Euis Ratnasari; Suripto Muh Zulkifli; Rinaldi Sri Herlambang; Adi Suprayoga; Andri Irawan; Cahyana Cahyana; Rizqi Ikhwanudin Rofif; Nofa Nugraha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Generation Z refers to the demographic group consisting of individuals born between the mid-1990s to the mid-2010s. This generation is also known as